2019
DOI: 10.2754/avb201988030315
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative comparison of two kits for DNA extraction from canned tuna

Abstract: The most common methods that can be used for species identification of tuna include methods based on detection of species-specific DNA via the polymerase chain reaction (PCR) method. The problem with DNA detection in processed products is the possibility of DNA fragmentation during the technological process. The quantity and quality of extracted DNA is a crucial step for species identification based on the DNA analysis. In this study, two DNA extraction methods (DNeasy Blood & Tissue Kit and DNeasy mericon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…All four extraction methods produced signifcantly diferent DNA concentration values except for DNeasy + PC and DNeasy MF, according to the Kruskal-Wallis H test with the post hoc Dunn's test (p < 0.05). Te signifcantly higher DNA concentration obtained with the DNeasy method as compared to the DNeasy MF method is consistent with a prior study comparing DNA extraction kits for canned tuna [28]. Similarly, Zahn et al [29] reported signifcantly higher DNA concentrations for shark cartilage samples extracted with the DNeasy method as compared to the DNeasy + PC method.…”
Section: Dna Sequencing and Species Identifcationsupporting
confidence: 86%
See 2 more Smart Citations
“…All four extraction methods produced signifcantly diferent DNA concentration values except for DNeasy + PC and DNeasy MF, according to the Kruskal-Wallis H test with the post hoc Dunn's test (p < 0.05). Te signifcantly higher DNA concentration obtained with the DNeasy method as compared to the DNeasy MF method is consistent with a prior study comparing DNA extraction kits for canned tuna [28]. Similarly, Zahn et al [29] reported signifcantly higher DNA concentrations for shark cartilage samples extracted with the DNeasy method as compared to the DNeasy + PC method.…”
Section: Dna Sequencing and Species Identifcationsupporting
confidence: 86%
“…A previous study reported that the DNA extraction method and packing medium greatly infuenced the quality and quantity of DNA isolated from canned tuna [27]. Because of the wide variety of packing media (e.g., oil, water, salt, and other ingredients) used in the industry, canned tuna may contain varying amounts of PCR inhibitors that can negatively impact the sensitivity of the PCR reaction [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 a Servusová a spol. 21 , kteří úspěšně izolovali DNA ze syrové i tepelně opracované svaloviny tuňáka žlutoploutvého (Thunnus albacares). Dosažené výsledky izolace DNA pro syrovou svalovinu byly řádově srovnatelné s našimi (51 ng μl -1 ; A 260 /A 280 = 1,8).…”
Section: Výsledky a Diskuseunclassified
“…V práci Servusová a spol. 21 , kde byly porovnávány dva komerční kity (DNeasy ® mericon Food Kit a DNeasy ® Blood & Tissue Kit) bylo prokázáno, že DNeasy ® mericon Food Kit je vhodnější pro PCR analýzu ryb. Z výsledků experimentů bylo zřejmé, že amplifikace proběhla lépe ve vzorcích izolovaných tímto kitem, přestože koncentrace změřená spektrofotometricky byla nižší než u druhého kitu; DNeasy ® mericon Food Kit tak byl označen jako lepší pro izolace DNA z konzervovaných rybích výrobků.…”
Section: Název Produktuunclassified